1988
DOI: 10.1177/036354658801600316
|View full text |Cite
|
Sign up to set email alerts
|

On the epidemiology of running injuries

Abstract: Using a survey questionnaire design, we investigated the incidence, site, and nature of jogging injuries among all participants of a popular 16 km race. The response rate was 83.6%. Of 4,358 male joggers, 45.8% had sustained jogging injuries during the 1 year study period, 14.2% had required medical care, and 2.3% had missed work because of jogging injuries. Occurrence of jogging injuries was independently associated with higher weekly mileage (P less than 0.001), history of previous running injuries (P less t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
192
7
26

Year Published

1989
1989
2019
2019

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 330 publications
(240 citation statements)
references
References 19 publications
15
192
7
26
Order By: Relevance
“…In conjunction with the positive effects of running on health and fitness, it is important to consider the risk of a running-related injury (RRI). Research has shown that the incidence of RRI is high; incidence rates of RRI vary from 30% to 79%, 3,[11][12][13][14]24,28 and from 7 to 59 RRIs per 1000 hours of running. 3,11,12,19 Most RRIs are overuse injuries of the lower extremity.…”
Section: Copyrightmentioning
confidence: 99%
“…In conjunction with the positive effects of running on health and fitness, it is important to consider the risk of a running-related injury (RRI). Research has shown that the incidence of RRI is high; incidence rates of RRI vary from 30% to 79%, 3,[11][12][13][14]24,28 and from 7 to 59 RRIs per 1000 hours of running. 3,11,12,19 Most RRIs are overuse injuries of the lower extremity.…”
Section: Copyrightmentioning
confidence: 99%
“…Several civilian studies (40,115,147,168) and observational military investigations (117,250) have identified higher running mileage as an injury risk factor. An obvious strategy is to reduce the amount of running performed by service members although there are concerns about how this would influence aerobic fitness.…”
Section: (1) Training-related Strategiesmentioning
confidence: 99%
“…A key question in developing optimal physical training programs for units with a major load carriage missions is the amount of road marching to include into the total program. Some road marching is probably needed to meet specificity requirements (35) while excessive marching may be costly in terms of training time and increased risk of injury (27,33). Thus, the purpose of the present study was to examine the monthly frequency of load carriage training needed to improve performance on a strenuous road march.…”
Section: Introductionmentioning
confidence: 99%